UNDERSTANDING RISK DISSEMINATION: AN OVERVIEW IN SOYBEAN AND CORN MARKETS - Tonin, Julyerm Matheus (2021)
This paper provides an overview of the research literature on risk transmission for the corn and soybean markets. The systematic review includes research, structure and synthesis of empirical studies using terms such as contagion, transmission and spillover to assess the spread of risk across markets. The featured topics include the review of the main analytical perspectives of agricultural market interaction with other markets and theoretical developments in price risk analyses. Exogenous changes to the agricultural market, such as the financial crisis, rise of biofuels and financialization of commodities, are pointed out in the literature as vectors of risk transmission to the corn and soybean markets. The results show the increase of studies that evaluate spillover, with the predominant use of the multivariate GARCH approach, focused mainly on interrelations between the food and energy markets.